Is a Schizoanalysis of Cinema Possible? / Une schizoanalyse du cinéma est-elle possible ? - Buchanan, Ian (Cinémas)

(untitled) (Cinémas, 2006)
AbstractIs a schizoanalysis of cinema possible? This question arises from the observation that there is no apparent continuity between Deleuze’s two-volume collaboration with Guattari, Anti-Oedipus and A Thousand Plateaus, and the books he wrote afterwards, Cinema 1 and Cinema 2. It is also prompted by the observation that Anti-Oedipus and A Thousand Plateaus seem to rely a great deal on cinema in order to develop and exemplify the many new concepts these books introduce. This paper highlights three such instances in their work. The fact is, Deleuze and Guattari claim that the core schizoanalytic concepts of the body without organs, the abstract machine and assemblage can account for “all things”; as such, these concepts must account for cinema too. It is the sheer expansiveness of these concepts that makes them attractive to cinema studies. Not only that, they promise a way of engaging with cinema that isn’t reliant on the fictions of identification, recognition and fantasy. In this sense we are permitted to assume that to some degree Cinema 1 and Cinema 2 are already schizoanalytic, albeit in ways we have yet to properly understand. The author makes a direct link between cinema and schizoanalysis by highlighting the significance of delirium to both. This paper argues that the royal road to a schizoanalysis of cinema is via delirium rather than dream or fantasy. It goes on to show how Deleuze and Guattari’s formalisation of delirium as a “regime of signs” can be used to inaugurate a new kind of semiology of cinema.